Promoting Clinical Breast Examination as A screening Tool for Breast Cancer in Iraq - Al-Alwan, nada; mualla, Faisal (Iraqi National Journal of Nursing Specialties, 2014)
Breast cancer constitutes about one fourth of the registered cancer cases among the Iraqi population (1)and it is the leading cause of death among Iraqi women (2). Each year more women are exposed to the viciousramifications of this disease which include death if left unmanaged or the negative sequels that they wouldexperience, cosmetically and psychologically, after exposure to radical mastectomy.The World Health Organization (WHO) documented that early detection and screening, when copedwith adequate therapy, could offer a reduction in breast cancer mortality; displaying that the low survival ratesin less developed countries, including Iraq, is mainly attributed to the lack of early detection programs coupledwith inadequate diagnostic and treatment facilities (3). Although mammography machines, as main screeningtools for breast cancer, are available in the major hospitals in each province in Iraq, yet those are mainly usedfor diagnostic purposes in patients who present with palpable breast lumps. Obviously, due to cost effectivemeasures, lack of resources and the economical challenges that Iraq is facing, it is not expected that theauthorities could provide mammography devices across every health care centre in the country to be used forscreening of all Iraqi women.Accordingly, promoting other feasible tools could support in solving that dilemma. Clinical BreastExamination (CBE) for women, by highly trained health care providers in Primary Health Care Centers, alongwith diagnostic mammography in the major hospitals for referred cases, could offer cost effective approachesfor early detection of breast cancer in Iraq. The resources required to provide these services are within thereach of all countries with limited resources(4).The issue of raising awareness on breast cancer and its early detection measures needs to be addressed.Observations reported in Iraqi studies obviously reflect the the limited knowledge of the general populationabout the disease, its preventive measures and their ignorance regarding the significance of CBE and earlymedical consultation (5, 6). Public health awareness campaigns should be endorsed by policy makers to encourage every Iraqi women to look for abnormal signs and symptoms in their breasts and to seek medicaladvice promptly.